In vitro plant regeneration of potato (Solanum tuberosum L.) at the rate of different hormonal concentration - Shahriyar, Sayeed; Akram, Soleh; Khan, Koushik; Miya, Md Faruk; Sarkar, Md Abdur Rauf (Asian Journal of Medical and Biological Research, 2015)
One of the goals of the experiment is to standardization of HgCl2 treatment for explants sterilization. The objectives also include developing a reproducible cost effective protocol for large scale production of Solanum tuberosum of Cardinal variety plantlets from selectively better clones through plant in vitro propagation methods. Selection of growth regulators for proper multiple shoots regeneration, elongation and root induction. To produce genetically uniform plantlets within a short time capable surviving in natural condition raised in in vitro environment. Shoot tip and nodal segment explants from field grown plants were used as experimental materials in this investigation. All explants were cultured on Murashige and Skoog medium supplemented with various plant growth regulators. For surface sterilization of explants, HgCl2 (0.1%) for 2 minutes was found to be most effective for complete destroying of surface pathogens and getting healthy tissues. Shoot regeneration was observed from both shoot tips and nodal explants for the studied plant. Maximum number of shoot per culture (17) was recorded and it also obtained the highest average length of the shoot (5cm) in Murashige and Skoog medium containing no hormone. On the other hand 6-benzyl amino purine (0.2mg/l) in 3 media showed the highest rate of shoot multiplication (73%) and the highest average length (4cm). In case of Gibberellic acid (0.1mg/l) in Murashige and Skoog media showed its highest rate of shoot regeneration (82%) and the highest average length (4.5cm). From the overall experiment it was observed that shoot tips are more responsive for micro propagation. In root induction Murashige and Skoog medium supplemented with different concentration (0.5, 1, 1.5 and 2mg/l) of indol-3-acetic acid and kinetin. Indol-3-acetic acid and kinetin (1.5+1.5 mg/l) showed its lowest rate of root regeneration (40%) and the average length of the root (1.5 cm). On the contrary Murashige and Skoog medium with no hormone showed the rate of root regeneration (96%) and the highest average length of the root (2.5 cm). The supplemented Murashige and Skoog media with no hormone showed the best performance for root regeneration. Asian J. Med. Biol. Res. June 2015, 1(2): 297-303